2010
DOI: 10.1128/ec.00203-09
|View full text |Cite
|
Sign up to set email alerts
|

RNA Interference Silencing of a Major Lipid Droplet Protein Affects Lipid Droplet Size in Chlamydomonas reinhardtii

Abstract: Eukaryotic cells store oils in the chemical form of triacylglycerols in distinct organelles, often called lipid droplets. These dynamic storage compartments have been intensely studied in the context of human health and also in plants as a source of vegetable oils for human consumption and for chemical or biofuel feedstocks. Many microalgae accumulate oils, particularly under conditions limiting to growth, and thus have gained renewed attention as a potentially sustainable feedstock for biofuel production. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
381
3
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 372 publications
(421 citation statements)
references
References 41 publications
(57 reference statements)
27
381
3
3
Order By: Relevance
“…NJ-1 may be suitable for outdoor mass culture during the whole seasons of the year in warm temperate regions due to its relatively wide range of growth temperature and natural settling. Many microorganisms (Gouda et al 2008) and microalgae (such as diatoms and green algae) are capable of accumulating large amounts of TAGs in oil droplets under environmental stress conditions (Moellering and Benning 2010). The oil droplets in Scenedesmus NJ-1 may also serve as a reserve of energy in the form of TAGs.…”
Section: Discussionmentioning
confidence: 99%
“…NJ-1 may be suitable for outdoor mass culture during the whole seasons of the year in warm temperate regions due to its relatively wide range of growth temperature and natural settling. Many microorganisms (Gouda et al 2008) and microalgae (such as diatoms and green algae) are capable of accumulating large amounts of TAGs in oil droplets under environmental stress conditions (Moellering and Benning 2010). The oil droplets in Scenedesmus NJ-1 may also serve as a reserve of energy in the form of TAGs.…”
Section: Discussionmentioning
confidence: 99%
“…In higher plants, this is usually in the form of starch (Diaz et al, 2005;Wingler et al, 2006), and Peng et al (2007) described increased transcript levels of two genes involved in starch biosynthesis in Arabidopsis (Arabidopsis thaliana) under nitrogen starvation. In the fresh water green alga Chlamydomonas reinhardtii, on the other hand, excess carbon is reportedly directed to fatty acid biosynthesis (Wang et al, 2009;Moellering and Benning, 2010), and Miller et al (2010) found increased expression of genes involved in lipid biosynthesis in C. reinhardtii when nitrogen was not available. Diatoms are known to store carbon as chrysolaminaran (a b-1,3-glucan) or as lipids (Armbrust et al, 2004;Kroth et al, 2008); however, proteins directly related to the synthesis or degradation of these compounds were not identified in this study.…”
Section: Interspecies Comparisonmentioning
confidence: 99%
“…N deprivation for 48 h showed the greatest difference in RNA levels compared with the N-replete cultures. Based on this basic analysis and our previous timecourse study of lipid droplet formation and TAG accumulation (Moellering and Benning, 2010), a 48-h period of N deprivation was chosen to compare global transcript levels in N-replete and N-deprived cells.…”
Section: Defining Conditions For N Deprivation Of C Reinhardtiimentioning
confidence: 99%
“…At this time, Chlamydomonas reinhardtii is the premier microalgal molecular model for this analysis. As such, the formation of lipid droplets following nitrogen (N) deprivation has recently been documented in detail (Wang et al, 2009;Moellering and Benning, 2010). Although C. reinhardtii is not under direct consideration for the production of biomass as a biofuel feedstock, the analysis of its metabolism and physiology is expected to provide basic insights into mechanisms of TAG accumulation relevant to other microalgae at least of the green algal phylum.…”
mentioning
confidence: 99%
See 1 more Smart Citation